ERK/Nrf2 pathway activation by caffeic acid in HepG2 cells alleviates its hepatocellular damage caused by t-butylhydroperoxide-induced oxidative stress - Sung-Yong Yang; Min Cheol Pyo; Mi-Hyun Nam; Kwang-Won Lee (BMC, 2019)
Abstract Background Several studies have found that caffeic acid (CA), a well-known phytochemical, displays important antioxidant and anti-cancer activities. However, no evidence exists on the protective effect and its mechanisms that CA treatment alone has against oxidative stress induced by tert-butyl hydroperoxide (t-BHP) in HepG2 cells. Methods Hepatoprotective activities such as cell viability, mRNA expression, and report gene assay were measured using HepG2 cell. Three types of genes and proteins related with detoxification in liver were used for measuring the hepatoprotective effects. Statistical analysis was performed using one-way ANOVA test and differences among groups were evaluated by Tukey's studentized range tests. Results The present study indicate that treatment with CA up-regulates heme oxygenase-1 (HO-1) and glutamate-cysteine ligase (GCL) mRNA and protein expressions in a CA-dose-dependent manner. In addition, translocation of nuclear factor-E2 p45-related factor (Nrf2) from the cytoplasm to the nucleus and phosphorylation of extracellular signal-regulated kinase, ERK and c-Jun N-terminal kinase, JNK which have been shown to be involved in mitogen-activated protein kinases, MAPKs are significantly enhanced by CA treatment. Furthermore, in cell nuclei, CA enhances the 5'-flanking regulatory region of human antioxidant response element (ARE) and activates the ARE binding site. Conclusion Therefore, CA proved to be a stimulant of the expression of detoxification enzymes such as HO-1, GCLC, and GCLM through the ERK/Nrf2 pathway, and it may be an effective chemoprotective agent for protecting liver damage against oxidative damage. Graphical abstract